2018
DOI: 10.24843/itepa.2018.v07.i04.p05
|View full text |Cite
|
Sign up to set email alerts
|

Stabilitas Mikroemulsi Vco Dalam Air Pada Variasi HLB Dari Tiga Surfaktan Selama Penyimpanan

Abstract: Microemulsion is a dispersion system developed from emulsions, which is an oil dispersion system in water, stabilized by a surfactant. Oil-in-water (o/w) microemulsion is an emulsion system suitable for encapsulation and carrier of lipophilic components in the beverage industry. The food grade microemulsion formulation is limited by the type of surfactant that can be used. This research aims to obtain an o/w microemulsion formulation which is stable during storage using three surfactants. In this study, 3 type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0
5

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 3 publications
0
1
0
5
Order By: Relevance
“…Microemulsion testing against heating is the most critical test. High temperature causes dehydration increase in the hydrophilic part so that the emulsifier molecules aggregate and the solution became cloudy (Indirasvari et al, 2018).The result of this study showed that all formulations were able to produced stable microemulsions due to turbidity index value less than 1%, transparent appearance and no separation. The best treatment in first stage is the S3 formula (98:0, 5:1, 5) because it has the lowest average turbidity, so it is continued in the second stage research.…”
Section: Surfactant Mixed Formulation In Microemulsion (O/w)mentioning
confidence: 80%
“…Microemulsion testing against heating is the most critical test. High temperature causes dehydration increase in the hydrophilic part so that the emulsifier molecules aggregate and the solution became cloudy (Indirasvari et al, 2018).The result of this study showed that all formulations were able to produced stable microemulsions due to turbidity index value less than 1%, transparent appearance and no separation. The best treatment in first stage is the S3 formula (98:0, 5:1, 5) because it has the lowest average turbidity, so it is continued in the second stage research.…”
Section: Surfactant Mixed Formulation In Microemulsion (O/w)mentioning
confidence: 80%
“…Pada pH 4,5, pH 5,5 dan pH 6,5 mikroemulsi minyak atsiri cempaka putih masih stabil yaitu memiliki nilai indeks turbiditas kurang dari 1% dan kenampakan transparan. Indirasvari et al (2018) melaporkan derajat keasaman (pH) pada pH 3,5 dan pH 4,5 tidak berpengaruh terhadap mikroemulsi VCO. Surfaktan non ionik digunakan dalam pembuatan mikroemulsi VCO, sehingga bagian hidrofilik surfaktan tidak terdisosiasi oleh pengaruh…”
Section: Stabilitas Mikroemulsi Minyak Atsiri Cempaka Putih Selama Pe...unclassified
“…Hal ini disebabkan oleh Tween 80 dan Span 80 dapat mengemulsi senyawa bioaktif yang terlarut pada ekstrak bunga kenikir, dimana senyawa bioaktif bunga kenikir umumnya bersifat non polar (Cahyana et al, 2021). Indirasvari et al (2018) menyatakan bahwa surfaktan dengan HLB 13 tetap stabil pada senyawa non polar. Jumlah rendemen yang diperoleh juga berhubungan dengan kadar air enkapsulat, dimana kadar air bahan yang tinggi menyebabkan rendemen yang diperoleh rendah akibat terjadi penguapan pada saat proses pemanasan.…”
Section: Rendemenunclassified
“…Span 80 (HLB = 4,3) bersifat hidrofobik kemungkinan berada dibagian dalam yang terdiri dari sorbitol terester sebagian dengan mono dan dianhidrida asam oleat, sedangkan Tween 80 (HLB = 15) kemungkinan berada dibagian luar yang terdiri dari sorbitan polioksilat dan asam oleat. Gugus hidrofiliknya adalah polieter yang disebut juga gugus polioksietilen (polimer dari etilen oksida) (Indirasvari et al, 2018).…”
Section: Rendemenunclassified
See 1 more Smart Citation